Influence of germination on bioaccessible iron and calcium in pearl millet (Pennisetum typhoideum) - Suma, P. Florence (Springer India, 2011)
Pearl millet is the staple for economically poorer section of the world’s population and improving its mineral bioaccessibility is one of the important approaches to promote its utilization. In the absence of any data on the bioaccessible mineral content from commercially available millet, two varieties namely Kalukombu (native) and Maharastra Rabi Bajra (hybrid) were germinated and its effect on the bioaccessible iron and calcium content was explored using an in-vitro method which simulates gastrointestinal digestion. The millet was germinated for 72 h to facilitate maximum mineral extraction. The bioaccessibility of iron and calcium was considerably enhanced upon sprouting. This higher bioaccessibility could be attributed to decrease in antinutritional factors like phytate and oxalate as a result of germination. Changes in mineral and antinutrient content during sprouting led to significant variations in the antinutrient/mineral molar ratios which had a positive impact on the bioaccessible mineral content. Use of tap water for soaking prior to germination revealed contamination of the millet with iron. Contaminant iron in Kalukombu variety appeared to be less accessible; while the same was potentially bioaccessible in Maharashtra Rabi Bajra variety. Hence bioaccessibility of iron depends on the form in which it is present. The actual bioaccessibility of contaminated iron needs to be further investigated.